Sustainability in irrigation management in six agro-exporting companies of "Carica papaya L" in the department of Petén, Guatemala - Martínez-Cuestas, Marco Antonio (2024)
In the department of Petén, Guatemala, there are agro-exporting companies producing papaya (Carica papaya L.) with significant water requirements. However, the extraction of water can potentially lead to the depletion of groundwater and surface water sources in the medium term. Therefore, the objective of this research was to evaluate the sustainability of irrigation systems in six agro-exporting papaya (Carica papaya L.) companies in the department of Petén, Guatemala. For the analysis of sustainability in the studied companies, descriptive and inferential statistics were used, applying measures of dispersion, variability, skewness, and normality tests of data. With this information, a model for evaluating the sustainable management of water resources was proposed. Data collection instruments included observation, a structured questionnaire, an unstructured questionnaire, and a registration form with experimental indicators that allowed for the proposal of a model with an index to assess sustainability. The application of the model resulted in the Irrigation Sustainable Impact Index with a rating of 0.64, which places the irrigation systems of the studied companies in the category of low sustainability. Therefore, it is recommended to implement management systems based on plans for vegetative restoration in water recharge areas, studies of surface and groundwater quality, as well as environmental impact assessments, and to foster a culture of sustainable education and efficient water use for irrigation.